2013
DOI: 10.3126/ije.v2i1.9217
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activityof Aqueous And Ethanolic Leaf Extracts Of Vernonia Amygdalina On Selected Species Of Gram Positive And Gram Negative Bacteria

Abstract: The phytochemical screening and antibacterial activity of ethanolic and Methanolic leaves extract of Vernonia amygdalina against five clinical isolates (Staphylococcus aureus, E. coli, Pseudomonas species, Salmonella species and Proteus species) was determined using standard method of analysis. The results of the antibacterial activity of ethanol, methanol and aqueous extract of leaves of V. amygdalina have diameters ranging between 0.4 to 10mm. The plant extracts from the plants had profound activities agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…A literature search performed on documented anti-typhoid activity of the plants used in formulating these preparations such as (Carica papaya [66], Vernonia amygdalina [67][68][69] Table 1) showed that all the 8 plants contained flavonoids, while 7 contained alkaloids, 6 out of the eight plants contained tannins, saponins and glycosides as secondary metabolites [70][71][72][73][74][75][76][77]. The antityphoid activity may well be due to the presence of these phytoconstituents, but further studies may need to be done to ascertain this.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search performed on documented anti-typhoid activity of the plants used in formulating these preparations such as (Carica papaya [66], Vernonia amygdalina [67][68][69] Table 1) showed that all the 8 plants contained flavonoids, while 7 contained alkaloids, 6 out of the eight plants contained tannins, saponins and glycosides as secondary metabolites [70][71][72][73][74][75][76][77]. The antityphoid activity may well be due to the presence of these phytoconstituents, but further studies may need to be done to ascertain this.…”
Section: Discussionmentioning
confidence: 99%
“…Both the roots and leaves are utilized in phytomedicine for the treatment of kidney diseases, fever, stomach discomfort and hiccups, among others [20]. Bukar et al, (2013) a rmed that the sensitivity of V. amygdalina was more towards gram positive bacteria compared to the of gram-negative bacteria; However, other researchers revealed that the activity of V. amygdalina on gram-negative bacteria was comparable to its effect towards the grampositive species [18,21]. For example, methanol extract of V. amygdalina affected not only the growth of gram-positive bacteria such as B. subtilis, B. cereus, M. kristinae, B. pumilus, S. aureus and E. cloacae but exhibited potency against gram-negative bacteria which include Proteus vulgaris, Klebsiella pneumoniae, Shigella dysenteriae, Pseudomonas aeruginosa, and E. coli [22,23].…”
Section: Typhoid Fevermentioning
confidence: 99%
“…Penelitian terhadap aktivitas antimikroba ekstrak daun afrika (Afolabi et al, 2014) yang dilakukan menunjukkan hasil yang positif terhadap bakteri aktivitas Streptococcus mutans, Staphylococcus aureus dan Lactobacillu acidophilus. Ekstrak daun afrika memiliki aktivitas antibakteri yang mampu membunuh bakteri gram posirif dan gram negatif (Erasto, 2008;Bukar et al, 2013), antihelmintes (Nalule et al, 2013), antipiretik antinosiseptik (Adiukwu et al, 2013).…”
Section: Pendahuluanunclassified